2018
DOI: 10.1101/323790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-photon light-sheet fluorescence microscopy

Abstract: We present the first demonstration of three-photon excitation light-sheet fluorescence microscopy. Light-sheet fluorescence microscopy in single-and two-photon modes has emerged as a powerful wide-field, low photo-damage technique for fast volumetric imaging of biological samples. We extend this imaging modality to the three-photon regime enhancing its penetration depth. Our present study uses a standard conventional femtosecond pulsed laser at 1000 nm wavelength for the imaging of 450 µm diameter cellular sph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Since the first demonstrations of 3PM for in vivo brain imaging (Horton et al, 2013; Ouzounov et al, 2017), a number of research groups have successfully adopted and developed the technology (Chen et al, 2018; Escobet-Montalbán et al, 2018; Odríguez, 2018; Perillo et al, 2017; Rowlands et al, 2017; Takasaki et al, 2019b; Weisenburger et al, 2019; Yildirim et al, 2019), propelled by the commercially available lasers and microscopes. To facilitate 3PM applications, here we provide a quantitative characterization of three-photon deep-brain calcium imaging, with a side-by-side comparison to 2PM with 920 nm excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first demonstrations of 3PM for in vivo brain imaging (Horton et al, 2013; Ouzounov et al, 2017), a number of research groups have successfully adopted and developed the technology (Chen et al, 2018; Escobet-Montalbán et al, 2018; Odríguez, 2018; Perillo et al, 2017; Rowlands et al, 2017; Takasaki et al, 2019b; Weisenburger et al, 2019; Yildirim et al, 2019), propelled by the commercially available lasers and microscopes. To facilitate 3PM applications, here we provide a quantitative characterization of three-photon deep-brain calcium imaging, with a side-by-side comparison to 2PM with 920 nm excitation.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that by relying on such higher order nonlinear process, fluorescence is confined to a smaller volume, reducing out-of-focus light. 17,22 Novel laser sources have recently been developed to generate high energy pulses to optimize the absorption of three photons. Such ultrashort Compressive sensing is demonstrated a posteriori, by using 5% and 15% of the recorded Hadamard patterns and minimizing to the l1 norm.…”
Section: Three-photon Trafixmentioning
confidence: 99%
“…However, conventional Ti:Sapphire lasers can still be used to excite fluorophores at the high frequency end of the visible spectrum. 22 To demonstrate that TRAFIX can potentially be used in 3P excitation mode, we imaged 2.1 um blue fluorescent microspheres. To obtain a high power per unit area and achieve enough photon density to generate 3P excitation, the FOV was reduced to only 20 µm × 20 µm.…”
Section: Three-photon Trafixmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIR excitation allows for improved penetration into biological samples and minimises scattering compared to visible excitation 25 . Twophoton light sheet fluorescence microscopy (2P-LSFM) has been used for live imaging of zebrafish development 7 , and more recently three-photon light sheet fluorescence microscopy (3P-LSFM) has been used in conjunction with Bessel beam illumination for 3D imaging with high-contrast and low photodamage in highly scattering cell spheroids over a large FOV 26 . While with one-photon (1P) excitation the out-of-focus side-lobes in Airy and Bessel beams cause a reduction of image contrast, with 2P excitation, due to the quadratic dependence on incident intensity, this issue gets largely resolved.…”
Section: Introductionmentioning
confidence: 99%